Hubungan Karakteristik Ibu Terhadap Status Gizi Balita di Wilayah Puskemas Imbanagara Kabupaten Ciamis - Niklah Zaidah; Muhammad Girza Fathwa A; Ignatius Hapsoro W (Universitas Malahayati Lampung, 2024)
ABSTRACT Nutritional status greatly affects the growth and development of under-five children. Nutritional status also affects the intelligence of under five children. Nutritional problems are a health problem of global concern. UNICEF states that until 2020 there is no single country that can reach the global nutrition targets that have been set. This research is an observational study, Quantitative, with a design used in this study is a case control. Using univariate, bivariate, multivariate analysis. There is a relationship between maternal age and nutritional status of toddlers p=0.000 (p0.05) with a correlation coefficient of 0,416 including a moderate relationship, there is a relationship between maternal knowledge and nutritional status of toddlers p=0,000 (p0.05) with a correlation coefficient of 0.372 including a moderate relationship, there is a relationship between maternal education and nutritional status of toddlers p=0,003 (p0.05) with a correlation coefficient of 0.179 including a very low relationship, there is no significant relationship between maternal income and the nutritional status of children under toddlers p=0.047 (p0.05) with a correlation coefficient of 0.047 including a very low relationship. There is no significant relationship between mothers' income and the nutritional status of under-five children, there is a significant relationship between mothers' age, mothers' knowledge, mothers' education on the nutritional status of under-five children in the Imbanagara community health centre. Keyword: Nutritional Status, Age, Knowledge, Education, Income ABSTRAK Status gizi sangat berpengaruh terhadap pertumbuhan dan perkembangan balita. Status gizi juga berpengaruh pada kecerdasan balita, permasalahan gizi merupakan masalah kesehatan yang masih menjadi perhatian secara global. UNICEF menyatakan hingga tahun 2020 tidak ada satupun negara yang dapat memenuhi target gizi global yang telah ditetapkan. Penelitian ini merupakan penelitian observasional yaitu Kuantitatif, dengan desain yang digunakan dalam penelitian ini adalah case control. Menggunakan analisis data univariat, bivariat, multivariat. Terdapat hubungan antara usia ibu dengan status gizi balita p=0,000 (p0,05) dengan Koefisien Korelasi 0,416 termasuk hubungan sedang , terdapat hubungan antara pengetahuan ibu dengan status gizi balita p=0,000 (p0,05) dengan Koefisien Korelasi 0,372 termasuk hubungan sedang, terdapat hubungan antara pendidikan ibu dengan status gizi balita p=0,003 (p0,05) dengan Koefisien Korelasi 0,179 termasuk hubungan sangat rendah, tidak ada hubungan yang signifikan antara pendapatan ibu dengan status gizi balita p=0,047 (p0,05) dengan Koefisien Korelasi 0,047 termasuk hubungan sangat rendah. Tidak terdapat hubungan yang signifikan antara pendapatan ibu dengan status gizi balita, terdapat hubungan yang signifikan antara usia ibu, pengetahuan ibu, pendidikan ibu terhadap status gizi balita di wilayah Puskesmas Imbanagara Kata Kunci: Status Gizi, Usia, Pengetahuan, Pendidikan, Pendapatan